Sunday houses the Sunday house - Hughey, Elizabeth (Iowa poetry prize., 2007)
In Sunday Houses the Sunday House, Elizabeth Hughey embraces the possibility that we can learn as much from objects as we can from other people, from the inanimate as much as the animate. Each poem descends upon a place and a time, takes a few notes, and then leaves quietly without slamming any doors. Sunday Houses the Sunday House reveals what the world is like when your attention is focused elsewhere, when your head is turned the other way.